Comparison of two novel swept-source optical coherence tomography devices to a partial coherence interferometry-based biometer - Tommy C. Y. Chan (Nature Portfolio, 2021)
Abstract To evaluate the repeatability and agreement of corneal and biometry measurements obtained with two swept-source optical coherence tomography (SSOCT) and a partial coherence interferometry-based device. This is a cross-sectional study. Forty-eight eyes of 48 patients had three consecutive measurements for ANTERION (Heidelberg Engineering, Germany), CASIAII (Tomey, Japan) and IOLMaster500 (Carl Zeiss Meditec, USA) on the same visit. Mean keratometry (Km), central corneal thickness (CCT), anterior chamber depth (ACD) and axial length (AL) were recorded. Corneal astigmatic measurements were converted into vector components—J0 and J45. Intra-device repeatability and agreements of measurements amongst the devices were evaluated using repeatability coefficients (RCs) and Bland–Altman plots, respectively. All devices demonstrated comparable repeatability for Km (p ≥ 0.138). ANTERION had the lowest RC for J0 amongst the devices (p ≤ 0.039). Systematic difference was found for the Km and J0 obtained with IOLMaster500 compared to either SSOCTs (p ≤ 0.010). The ACD and AL measured by IOLMaster500 showed a higher RC compared with either SSOCTs (p < 0.002). Systematic difference was found in CCT and ACD between the two SSOCTs (p < 0.001), and in AL between ANTERION and IOLMaster500 (p < 0.001), with a mean difference of 1.6 µm, 0.022 mm and 0.021 mm, respectively. Both SSOCTs demonstrated smaller test–retest variability for measuring ACD and AL compared with IOLMaster500. There were significant disagreement in keratometry and AL measurements between the SSOCTs and PCI-based device; their measurements should not be considered as interchangeable.